2022
DOI: 10.1021/acs.jpcc.1c10569
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sodium-Ion Dynamics and Characteristic Length Scales in Ion Conductivity in Aluminophosphate Glasses Containing Na2SO4

Abstract: Achieving high ion conductivity in glass-based Na-ion conducting materials for their applications as solid electrolytes in batteries is still challenging owing to the vague knowledge on the factors governing Na-ion dynamics. In the present study, an attempt has been made to identify the factors affecting the sodium-ion dynamics through structure and conductivity property correlation for the 37.5Na2O–37.5P2O5–15Al2O3–10NaF (FS-0; mol %) glass system with varied concentrations of Na2SO4. 31P, 27Al, and 23Na MAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…This clearly indicates that Na 2 SO 4 has a positive impact on conductivity for concentration >5 mol %. Several studies in the literature have reported that the addition of Na 2 SO 4 in phosphate glasses enhances the conductivity value. , Na 2 SO 4 decomposed in a glass structure and formed isolated SO 4 2– anions and Na + cations. Additionally, these large SO 4 2– anions accumulated in the channel regions surrounded by Na + cations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This clearly indicates that Na 2 SO 4 has a positive impact on conductivity for concentration >5 mol %. Several studies in the literature have reported that the addition of Na 2 SO 4 in phosphate glasses enhances the conductivity value. , Na 2 SO 4 decomposed in a glass structure and formed isolated SO 4 2– anions and Na + cations. Additionally, these large SO 4 2– anions accumulated in the channel regions surrounded by Na + cations.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is also important to note that conductivity depends on both the concentration and mobility of sodium ions, as expressed by the formula σ = nc μ (where σ is the conductivity, n is the sodium-ion concentration, μ is the mobility of the sodium ion, and c is the charge of the Na ion). Furthermore, several studies show that in glass samples, the structure plays a significant role in governing the conductivity of Na-ions and not their concentration alone. ,, A similar study on Na 3 Al 2 P 3 O 12 glasses where the concentration of NaF was increasing with decreasing Al 2 O 3 content showed that conductivity follows a non-monotonic pattern with Na-ion concentrationit increases up to a particular concentration of NaF (<10 mol %), following which it decreases . Accordingly, it is nontrivial to conclude that the change in conductivity is only due to the concentration of sodium ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the fraction of bridging oxygens can enhance the ionic conductivity from 3.7 × 10 −8 to 3.3 × 10 −7 S cm −1 at 100 °C. [ 113 ] Other tested glassy electrolytes for SIBs are Na 2 S‐P 2 S 5 , [ 114 ] Na 3 BS 3 , [ 115 ] Na 2 O‐P 2 O 5 ‐Al 2 O 3 ‐NaF‐Na 2 SO 4 , [ 116 ] Na 3 Al 2 P 3 O 12 ‐NaF, [ 117 ] sodium borophosphate, [ 118 ] sodium borosilicate, [ 119 ] NaCl‐Ga 2 S 3 ‐GeS 2 , [ 120 ] Na 3 PS 4 ‐Na 4 GeS 4 , [ 121 ] Na 2 O‐B 2 O 3 ‐SiO 2 ‐H 2 O, [ 122 ] etc. Further development of glass electrolytes with both high ionic conductivity and good machinability is required in the future.…”
Section: Am‐based Batteriesmentioning
confidence: 99%
“…Glass materials, known for their environmental friendliness, have been incorporated into a wide range of applications across the biological, optical, photonic, and energy sectors. [23][24][25][26][27] This versatility stems from their flexible thermal, optical, mechanical, and electrical properties, which can be precisely adjusted by altering their chemical composition. Glass substrates offer a number of benefits, including a smooth, transparent surface, simple handling, robustness, cost-effective, and chemical inertness.…”
Section: Introductionmentioning
confidence: 99%